The big bet: how much do Twitter´s changes affect scientific communication? - Arroyo-Machado, Wenceslao (Anuario ThinkEPI, 2023)
Since Elon Musk revealed his intention to buy Twitter, unease has spread throughout the scientific community. What was once the main channel for scientific communication has now seen its predominance threatened. This work analyzes the changes and consequences over the first months of Musk´s administration -a period that was marked by incessant changes and in which part of the community found sufficient grounds to migrate to other platforms, with Mastodon in the lead. In the field of research, the consequences are much more pronounced, characterized by a shift in data access policy. However, the long-term implications that Twitter´s Musk era will have for academia remain uncertain.
Keywords: Twitter; Scientific communication; Elon Musk; Mastodon; Altmetrics; API; Web3; Fediverse